2017
DOI: 10.1002/ccr3.1296
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myofibroblastic tumor of the esophagus presenting with hematemesis and melaena: a case report and review of literature

Abstract: Key Clinical MessageEsophageal inflammatory myofibroblastic tumors (IMT) are extremely rare, and the understanding on the clinical presentation is limited. IMT of esophagus should be considered as a differential diagnosis in the context of unexplained upper gastrointestinal bleeding and rapidly progressing dysphagia in young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…10 Meanwhile, hematemesis and melaena were also reported in the cases of esophageal IMT. [11][12] However, not all patients will appear the above symptoms and the patients in this study only showed the progressive dysphagia. At the same time, the difference also lies in imaging ndings.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…10 Meanwhile, hematemesis and melaena were also reported in the cases of esophageal IMT. [11][12] However, not all patients will appear the above symptoms and the patients in this study only showed the progressive dysphagia. At the same time, the difference also lies in imaging ndings.…”
Section: Discussionmentioning
confidence: 73%
“…[13][14] Endoscopy and radiological examinations are suit for esophageal IMT, but only 77% of the cases were found to be related to histopathology. 12,15,16 Variable spindle cell proliferation in a myxoid-to-collagenous stroma, in ammatory in ltrate composed primarily of plasma cells and lymphocytes, variable expression and lack of speci city of myo broblastic markers can be the evidence of diagnosis of IMT histopathologically. 4,7 Radical resection is recommended for IMT.…”
Section: Discussionmentioning
confidence: 99%
“… 3 They are a rare group of tumours originally described in the lung but later identified in multiple extrapulmonary anatomical sites. 4 In the urogenital system, the commonest site is the bladder, but isolated cases of IMT of kidney, renal pelvis and ureters have been reported. 5 The pathogenesis of IMTs is still obscure, but inflammatory reaction secondary to surgery, trauma, infection and even malignancy can be the cause.…”
Section: Discussionmentioning
confidence: 99%
“…Fever, dry cough and chest pain were found happened in pulmonary IMT patients [ 2 , 3 ], and dysphagia, reflux were the appearances of esophageal IMT [ 10 ]. Meanwhile, hematemesis and melaena were also reported in the cases of esophageal IMT [ 11 , 12 ]. However, not all patients will appear the above symptoms and the patients in this study only showed the progressive dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, since IMT has a high cellularity and predominant inflammatory cells, an elevated SUV max will be a pitfall in the differential diagnosis of IMT from malignancy [ 13 , 14 ]. Endoscopy and radiological examinations are suit for esophageal IMT, but only 77% of the cases were found to be related to histopathology [ 12 , 15 , 16 ]. Variable spindle cell proliferation in a myxoid-to-collagenous stroma, inflammatory infiltrate composed primarily of plasma cells and lymphocytes, variable expression and lack of specificity of myofibroblastic markers can be the evidence of diagnosis of IMT histopathologically [ 4 , 7 ].…”
Section: Discussionmentioning
confidence: 99%